Government and Private Collaboration in Coping with Covid-19 in Sorong City - Kamaluddin (International research journal of management, IT and social sciences, 2021)
Research on Muhammadiyah collaboration with the government is very important, the role of the State as the only single actor capable of carrying out everything is starting to lose its relevance at this time, therefore the role of the state must be minimized and strengthen the role of the private sector. One of the problems that befell the territory of Indonesia, especially. Most of the people of Sorong city feel the impact of the covid-19 and really need help from other parties, in this case Muhammadiyah is expected to play a role in collaborating with the government in the midst of the covid-19 in Sorong City. The results of this study suggest that the Muhammadiyah association has collaborated with the government in various forms of activity including: socializing the dangers of the Covid-19 disease, distributing masks, distributing hand sanitizers, distributing basic necessities, producing and spraying disinfectants in public facilities, houses of worship, schools. And other places that are considered prone to the spread of Covid-19. Although the activities carried out between Muhammadiyah and the government are not stated in a special MOU, activity carried out by Muhammadiyah always communicates and coordinates with the city government Sorong in dealing with Covid-19.